Tracking Control of a Spool Displacement in a Direct Piezoactuator-Driven Servo Valve System - Han, Chulhee; Hwang, Yong-Hoon; Choi, Seung-Bok (Frontiers in Materials, 2017)
This paper presents tracking control performances of a piezostack direct drive valve (PDDV) operated at various temperatures. As afirst step, a spool valve and valve system are designed operated by the piezoactuator. After briefly describing about operating principle, an experimental apparatus to investigate the effect of temperaturs on the performances is set up. Subsequently, the PDDV is installed in a large-size heat chamber equipped with electric circuits and sensors. A classical proportional-integral-derivative (PID) controller is designed and applied to control the spool displacement. In addition, a fuzzt algorithm is integrated with the PID controller to enhace performance of the proposed valve system. The tracking performance of a spool displacement is tested by increasing the teperature and exciting frequency up to 150°C and 200 Hz, respectively. It is shown that the tracking performance heavily depends on both the operating temperature and the excitation frequency.